PENERAPAN PRINSIP PENDIDIKAN ISALAM DALAM PENGEMBANGAN KURIKULUM SEKOLAH MENENGAH DI ERA DIGITAL - Hilal Solikin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Developing a secondary school curriculum in the digital era is a complex challenge that requires the integration of Islamic values as a moral and spiritual foundation. This research aims to investigate the application of Islamic education principles in developing secondary school curricula in the digital era, with a focus on the challenges and opportunities faced by educators in combining Islamic values with technological advances. The research methods used are literature analysis, library data collection, reading and taking notes, as well as managing research materials and case studies of curriculum implementation in several secondary schools. The research results show that the integration of Islamic values in the curriculum in the digital era requires a holistic approach that involves a deep understanding of Islamic teachings, development of technology-based skills, stakeholder involvement, and continuous training for educators. Despite facing various challenges, such as resistance to change and limited resources, there are also great opportunities to improve the quality of Islamic education in the digital era through implementing appropriate strategies and collaboration between schools, families and communities. These findings provide valuable insights for educators and policy makers in developing relevant and meaningful curricula for students in an increasingly complex digital era.